Dose Tailoring of Vancomycin Through Population Pharmacokinetic Modeling Among Surgical Patients in Pakistan - Munir, Muhammad Muaaz; Rasheed, Huma; Khokhar, Muhammad Imran; Khan, Rizwan Rasul; Saeed, Hafiz Asad; Abbas, Mateen; Ali, Mohsin; Bilal, Rabiea; Nawaz, Hafiz Awais; Khan, Abdul Muqeet; Qamar, Shaista; Anjum, Syed Muneeb; et al. (Frontiers in Pharmacology, 2021)
Background: Vancomycin is a narrow therapeutic agent, and it is necessary to optimize the dose to achieve safe therapeutic outcomes. The purpose of this study was to identify the significant covariates for vancomycin clearance and to optimize the dose among surgical patients in Pakistan. Methods: Plasma concentration data of 176 samples collected from 58 surgical patients treated with vancomycin were used in this study. A population pharmacokinetic model was developed on NONMEM® using plasma concentration-time data. The effect of all available covariates was evaluated on the pharmacokinetic parameters of vancomycin by stepwise covariate modeling. The final model was evaluated using bootstrap, goodness-of-fit plots, and visual predictive checks. Results: The pharmacokinetics of vancomycin followed a one-compartment model with first-order elimination. The vancomycin clearance (CL) and volume of distribution (Vd) were 2.45 L/h and 22.6 L, respectively. Vancomycin CL was influenced by creatinine clearance (CRCL) and body weight of the patients; however, no covariate was significant for its effect on the volume of distribution. Dose tailoring was performed by simulating dosage regimens at a steady state based on the CRCL of the patients. The tailored doses were 400 mg, 600 mg, 800 mg, and 1000 mg for patients with a CRCL of 20 mL/min, 60 mL/min, 100 mL/min, and 140 mL/min, respectively. Conclusion: Vancomycin CL is influenced by CRCL and body weight of the patient. This model can be helpful for dose tailoring of vancomycin based on renal status in Pakistani patients.